Hubungan Antara Karakteristik, Jenis Stroke, Dukungan Keluarga dan Kualitas Hidup Pasien Stroke di Rumah Sakit Univeritas Kristen Indonesia Jakarta - Asti Dwiyani, Benedicta; Astrid, Maria (STIKes Panti Rapih, 2021)
Background: Stroke often results in the burden and thus may affect the patient's quality of life. Objective: This study aims to determine the relationship between characteristics, type of stroke, family support, towards quality of life of stroke patients at UKI Hospital Jakarta. Methods: This study used correlative descriptive research method with cross sectional approach. There were 81 stroke patients choosen using purposive sampling technique. This study conducted from June to July 2020. This study used a questionnaire as a measuring tool. Result: The results revealed that most of the respondents were 25-65 years old (76,5%), male (67,9%), graduated from high school (71,8%), unemployee (63,0%), developed ischemic stroke (76,5%), good family support (79,0%) and good quality of life (86,4%). Chi-Square statistical test showed a significant relationship between work (p value 0.039), type of stroke (p value 0.000) to quality of life for stroke patients; however, there was no significant relationship between age (p value 0.777), gender (p value 0.307), education (p value 0.177), and family support (p value 0.582) to quality of life for stroke patients. Conclusion: A significant relationship between work, type of stroke to quality of life for stroke patients. There was no significant relationship between age, gender, education, and family support to quality of life for stroke patients. It is suggested that Hospital should provide health workers with counseling to the families of stroke patients in outpatient department such as reminding families through posters or leaflets about family support for stroke patients.